SIMULASI OPTIMALISASI TENAGA MEKANIK DI SERVICE YAMAHA KENJERAN SURABAYA - & Endang Pudji W, Dedi Putra Utama, Dira Ernawati, (JURNAL TEKMAPRO, 2015)
@font-face font-family: "Times New Roman"; @font-face font-family: "å®ä½"; @font-face font-family: "Calibri"; @font-face font-family: "MS Mincho"; p.MsoNormal margin-bottom: 10pt; line-height: 115%; font-family: "Times New Roman"; font-size: 11pt; p.MsoFooter margin-bottom: 10pt; line-height: 115%; font-family: "Times New Roman"; font-size: 11pt; span.msoIns text-decoration: underline; color: blue; span.msoDel text-decoration: line-through; color: red; div.Section0 AbstrackÂ ThisÂ studyÂ wasÂ doneÂ toÂ determineÂ theÂ optimalÂ numberÂ ofÂ mechanicalÂ tenaggaÂ .YamahaÂ KenjeranÂ SurabayaÂ isÂ oneÂ ofÂ theÂ famousÂ motorcycleÂ dealerÂ ofÂ YamahaÂ brandÂ products.Â InÂ YamahaÂ dealerÂ KenjeranÂ SurabayaÂ thereÂ areÂ manyÂ services,Â motorcycleÂ service,Â motorcycleÂ purchase,Â andÂ receiveÂ installmentÂ paymentsÂ orÂ installmentÂ motorcycle.InÂ thisÂ motorÂ dealersÂ areÂ problemsÂ inÂ termsÂ ofÂ service.Â TooÂ oftenÂ aÂ queueÂ waitingÂ forÂ customersÂ inÂ theÂ serviceÂ soÂ thatÂ customersÂ feelÂ uncomfortableÂ whenÂ havingÂ toÂ waitÂ aÂ longÂ timeÂ dueÂ toÂ queuing.Â ItÂ is,Â itÂ isÂ notÂ effectiveÂ ifÂ allowedÂ toÂ happenÂ becauseÂ itÂ wouldÂ leadÂ toÂ disappointmentÂ customersÂ whoÂ makeÂ themÂ moveÂ toÂ anotherÂ placeÂ ofÂ service.Â WithÂ theÂ reductionÂ ofÂ theÂ customer,Â indirectlyÂ motorcycleÂ dealersÂ willÂ experienceÂ aÂ declineÂ inÂ profits.WithÂ theÂ problemsÂ itÂ isÂ doneÂ researchÂ theÂ optimalÂ amountÂ ofÂ mechanicalÂ powerÂ withÂ queuingÂ models.Â QueuingÂ modelÂ isÂ aÂ processÂ associatedÂ withÂ theÂ arrivalÂ ofÂ aÂ customerÂ atÂ aÂ serviceÂ facility,Â thenÂ waitÂ inÂ aÂ lineÂ (queue).Â ModelÂ queueÂ isÂ processedÂ withÂ theÂ helpÂ ofÂ ARENAÂ SimulationÂ Software.TheÂ purposeÂ ofÂ thisÂ studyÂ wasÂ toÂ determineÂ theÂ optimalÂ amountÂ ofÂ mechanicalÂ energyÂ thatÂ canÂ serveÂ customersÂ optimally,Â afterÂ doingÂ thisÂ researchÂ itÂ canÂ beÂ concludedÂ forÂ theÂ amountÂ ofÂ mechanicalÂ energyÂ thatÂ mustÂ beÂ providedÂ aÂ numberÂ ofÂ 4Â peopleÂ mechanical,Â fromÂ previousÂ totalingÂ 3Â mechanics. Keywords:Â DeterminationÂ ofÂ theÂ amountÂ ofÂ mechanicalÂ energy,Â ArenaÂ SimulationÂ Software,Â ServicesÂ AbstrakÂ PenelitianÂ iniÂ diÂ lakukanÂ untukÂ mengetahuiÂ jumlahÂ tenaggaÂ mekanikÂ yangÂ optimalÂ .YamahaÂ kenjeranÂ SurabayaÂ merupakanÂ salahÂ satuÂ dealerÂ motorÂ ternamaÂ dariÂ brandÂ produkÂ Yamaha.Â DidalamÂ dealerÂ YamahaÂ kenjeranÂ SurabayaÂ terdapatÂ banyakÂ sekaliÂ pelayanan,Â service sepedaÂ motor,Â pembelianÂ sepedaÂ motor,danÂ menerimaÂ pembayaranÂ angsuranÂ atauÂ cicilanÂ sepedaÂ motor.PadaÂ dealerÂ motorÂ iniÂ terdapatÂ masalahÂ dalamÂ halÂ pelayanannya.Â SeringÂ sekaliÂ terjadiÂ antrianÂ menungguÂ pelangganÂ dalamÂ pelayanannyaÂ sehinggaÂ pelangganÂ merasaÂ kurangÂ nyamanÂ apabilaÂ harusÂ menungguÂ lamaÂ akibatÂ mengantri.Â HalÂ ini,Â sangatlahÂ tidakÂ efektifÂ bilaÂ dibiarkanÂ terusÂ terjadiÂ karenaÂ akanÂ mengakibatkanÂ kekecewaanÂ pelangganÂ yangÂ membuatÂ merekaÂ berpindahÂ keÂ tempatÂ service yangÂ lain.Â DenganÂ berkurangnyaÂ pelanggan,Â secaraÂ tidakÂ langsungÂ dealerÂ motorÂ akanÂ mengalamiÂ penurunanÂ keuntungan.DenganÂ adanyaÂ permasalahanÂ tersebutÂ makaÂ dilakukanÂ penelitianÂ jumlahÂ tenagaÂ mekanikÂ yangÂ optimalÂ denganÂ modelÂ antrian.Â ModelÂ antrianÂ adalahÂ suatuÂ prosesÂ yangÂ berhubunganÂ denganÂ kedatanganÂ seorangÂ pelangganÂ padaÂ suatuÂ fasilitasÂ pelayanan,Â kemudianÂ menungguÂ dalamÂ satuÂ baris(antrian).Â ModelÂ antrianÂ iniÂ diolahÂ denganÂ bantuanÂ ARENAÂ SimulationÂ Software.TujuanÂ penelitianÂ iniÂ adalahÂ untukÂ menentukanÂ jumlahÂ tenagaÂ mekanikÂ yangÂ optimalÂ sehinggaÂ dapatÂ melayaniÂ customer secaraÂ optimal,Â setelahÂ melakukanÂ penelitianÂ iniÂ makaÂ dapatÂ disimpulkanÂ untukÂ jumlahÂ tenagaÂ mekanikÂ yangÂ harusÂ disediakanÂ sejumlahÂ 4Â orangÂ mekanik,Â dariÂ sebelumnyaÂ yangÂ berjumlahÂ 3Â orangÂ mekanik.Â KataÂ kunciÂ :Â PenentuanÂ jumlahÂ tenagaÂ mekanik,Â ArenaÂ SimulationÂ Software,Â PelayananÂ Jasa